Peran Para Pihak Dalam Pengembangan Ekowisata di Kawasan Danau Toba Di Kawasan Hutan Dengan Tujuan Khusus Aek Nauli - Sylviani Sylviani; Nunung Parlinah; Ane Dwi Septina, S.Sos, MA; Deden Djaenudin; Endang Karlina; Bugi Kabul Sumirat (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2023)
The development of the Aek Nauli’s Forest Area with Special Purposes (KHDTK), as one of the national prioritytourist sites in the Lake Toba catchment area, needs to be carried out in support of North Sumatra ecotourism. Thisstudy examines the roles and functions of the parties involved in ecotourism management’s development. Primarydata were obtained from the results of discussions, FGD, and filling out questionnaires by respondents determinedpurposively from both government and community groups. The analysis was carried out using the stakeholderanalysis method to determine the parties’ roles and functions. The study results indicate that the most interested andinfluential parties are KLHK, BP2LHK Aek Nauli, BBKSDA North Sumatra, and BOPDT. The Parties which have low level of interest but have high influence are Bappenas, Kemenkomaritim, Kemenpar, Ministry of PUPR, BappedaNorth Sumatra, and Bappeda Simalungun Regency. The Parties with a high level of interest but low influence arthe surrounding community, such as Pokdarwis (Kelompok Sadar Wisata), and cooperation (koperasi). The partythat has a low level of interest and influence is PHRI. Coordination and communication are needed amongst theparties to carry out the national program in developing tourism priorities at KHDTK Aek Nauli correctly.Keywords: KHDTK Aek Nauli, The National Priority Tourist Site, Ecotourism, Danau Toba Area.